STRATEGI KOMUNIKASI PEMASARAN BATAMLICIOUZ MELALUI AKUN INSTAGRAM DALAM MEMASARKAN USAHA DI KOTA BATAM - Tunnisa, Faiza; Abadin, Sholihul (SCIENTIA JOURNAL, 2020)
The marketing communication strategy is very closely related to the marketing strategy adopted by a business. The marketing strategy adopted by Batamliciouz by using various features from Instagram itself, such as Live Streaming video, Story, posting videos and photos in the Batamliciouz Instagram Timeline by targeting the market for the people of Batam City who use social media Instagram, most followers are adults the age between 17-35 years. To find out the benefits of using the Batamliciouz account as a culinary marketing communication media in Batam, the purpose of marketing communication is to trigger the desire of potential followers to get the product marketed. The method used is descriptive qualitative method. sources of data obtained using interviews, observation, and documentation. While the theory used is the AIDA Theory where the Attention of a message that should get attention, becomes an Interest step a marketer is able to make a media of information so that it can contain attraction for consumers, raises Desire which is to trigger the desire of potential followers to get products marketed and leads to the level of Action is a step taken by a marketer in wanting the target to make a decision to buy.